Culinary Experience Towards Behavioral Of Domestic Tourists in Solo and Bandung, Indonesia - Kristanti, Monika; Jokom, Regina; Wijaya, Serli; Widjaja, Deborah C (KINERJA, 2018)
Solo and Bandung are two of the five major gastronomic destinations in Indonesia that are chosen by the Ministry of Tourism and Creative Economy . This research aimed to evaluate the effects of culinary experience quality towards behavioral intention through culinary experience satisfaction and destination experience satisfaction. A questionnaire involving 200 domestic tourists was completed and analyzed by using PLS path modelling. The ï¬ndings indicate that culinary experience quality significantly influences culinary experience satisfaction, however it will not significantly influence the satisfaction from destination experience. Moreover, it is also found that culinary experience satisfaction in Solo and Bandung does not have a significant effect on destination experience satisfaction. In addition, destination experience satisfaction has a positive and significant impact on domestic touristâ€™s behavioral intention, while, culinary experience satisfaction does not significantly influence their behavioral intention.Keywords: Culinary Experience Quality, Culinary experience satisfaction, Destination experience satisfaction, Touristâ€™s Behavioral intention.